African American education race, community, inequality and achievement ; a tribute to Edgar G. Epps - Allen, Walter Recharde; Spencer, Margaret Beale; O'Connor, Carla; Dano, Ophella; Epps, Edgar G., 1929- (Amsterdam ; Boston : JAI, 2002)
This volume considers African-American education in the 21st century through the lens of the Chicago School Tradition, at the University of Chicago. The Chicago School Tradition, among other emphases, stressed the optimistic view that all children who do not have serious physical or emotional impairments can do well in school, if provided access to effective teachers, sufficient resources and adequate opportunities to learn. On the occasion of Professor Edgar G. Epps' retirement from the University of Chicago, as Marshall Field IV Professor of Urban Education, this volume includes contributions from several generations of scholars influenced by his work to celebrate his career and contributions to educational research, policy and practice. More broadly, the volume adopts a holistic approach to examine the persistent challenges of deteriorating urban schools and poor educational outcomes for African American students. The volume seeeks to demonstrate how solutions may flow from educational research, theory, policy and practices conducted in the Chicago School Tradition.
Editor's welcome / Carol Camp Yeakey -- Foreword / Edmund W. Gordon -- Introduction / Walter R. Allen, Margaret Beale Spencer, Carla O'Connor -- Who will socialize African American students in contemporary public schools? / Diane S. Pollard -- African-American female students: their stories about academic achievement / Lisa Marie Pickens -- Zero tolerance policies and African American students / Ronald D. Henderson, Richard R -- Another shade of Brown / V.P. Franklin -- Identity and achievement: black ideology and the SAT in African American college students / Jacqueline Fleming -- Expectations of campus racial climate and social adjustment among African American college students / Sandra S. Smith, Mignon R. Moore -- Examining the perceptions of minority undergraduate students participating in a university-based research program / Henry T. Frierson, Rebecca A. Zulli -- The social utility scholarship: views of some African American scholars / Alford A. Young -- Ten hypotheses about what predicts student achievement for African American students and all other students: what the research shows / Reginald Clark -- The socialization of academic achievement and racial consciousness in an African American community-based youth program / Tracy R. Rone -- Education for African Americans in the information age / Cheryl B. Leggon -- Time out of bound: high school completion and work preparation among urban, poor, unwed African American fathers / Waldo E. Johnson -- Structural racism and community health: a theory-driven model for identity intervention / Margaret Beale Spencer, Vinay Harpalani, Tabitha Dell'Angelo -- Examining the career development behavior of inner city, special needs minority youth through the Philadelphia start-on-success scholars internship model demonstration program / Christopher W. Ashford, Joseph Y. Youngblood -- Male contraceptive use: a preliminary examination of factors that influence African American males' condom use / Regina Dixon-Reeves -- Black attitudes toward church integration / Clarence H. Thornton -- Beyond better "race" relations / Bruce R. Hare.
Based on a symposium held in 1998.
Includes bibliographical references and index.
Description based on print version record.
Keywords: African Americans -- Education -- Congresses; School integration -- United States -- Congresses; African Americans -- Employment -- Congresses; Conservatism -- United States -- Congresses; Affirmative action programs -- United States -- Congresses; African Americans -- education -- Congresses; Mainstreaming (Education) -- United States -- Congresses; African Americans -- Congresses; Employment -- United States -- Congresses; Social Change -- United States -- Congresses; Education; Ethnic minorities & multicultural studies; Education -- Research